Biofuel from vietnam heterotrophic marine microalgae: biodiesel and salvaging co-products (polyunsaturated fatty acids, glycerol and squalene) during biodiesel producing process - Hong, Dang Diem; Ha, Nguyen Cam; Thom, Le Thi; Tam, Luu Thi; Lan Anh, Hoang Thi; Hoai Thu, Ngo Thi (Academia Journal of Biology, 2016)
In this paper, we present the results relating to producing biodiesel and valuable added co- products, such us polyunsaturated fatty acids, glycerol and squalene from Vietnam heterotrophic marine microalga, Schizochytrium mangrovei, which was isolated from Phu Quoc Island, Kien Giang province, Vietnam in 2006-2008. The productivity of fatty acid methyl esters (FAME) from this microalga resulted in a yield of 89.2% based on algal oil and 46.7% based on algal biomass. The saturated fatty acids-SFA (biodiesel) was separated from fraction enriched in unsaturated fatty acids-PUFAs by urea complexation method at 10oC. Almost parameters of obtained biodiesel meet Vietnam Biodiesel B100 Standard. Docosahexaenoic acid (C22:6ω-3) in PUFA fraction reached up 72.00% of total fatty acid. Waste glycerol from biodiesel process can be used for cultivating S. mangrovei and Spirulina platensis BM. In spent biomass after biodiesel production process, squalene was detected approximately 50.21-80.10 ± 0.03 mg/g of spent biomass. The structure of squalene in residues of the biodiesel process was confirmed from its nuclear magnetic resonance spectra. The obtained results indicated that the cost of producing biodiesel from microalgae can be reduced if we fully exploit valuable added co-products above besides biodiesel. Citation: Dang Diem Hong, Nguyen Cam Ha, Le Thi Thom, Luu Thi Tam, Hoang Thi Lan Anh, Ngo Thi Hoai Thu, 2017. Biofuel from Vietnam heterotrophic marine microalgae: biodiesel and salvaging co-products (polyunsaturated fatty acids, glycerol and squalene) during biodiesel producing process. Tap chi Sinh hoc, 39(1): 51-60. DOI: 10.15625/0866-7160/v39n1.7129. *Corresponding author: ddhong60vn@yahoo.com Received 22 September 2016, accepted 20 March 2017